Geneologi Intelektual Reformasi Iran 1979 - Restu Restu; Muhammad Miftah Gunawan; Novita Dwi Nur Hidayati (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study describes the dynamics of the revolution led by Ayatollah Khomeini against the Shah Pahlavi regime and its impact on the community's socio-religious life. It examines the intellectual genealogy of the 1979 Iranian Revolution. This study discusses the transformation of the monarchical political system into an Islamic Republic triggered by the failure of development policies that are not in line with local traditional values. The research method used in this study is historical research with a qualitative-descriptive nature. Secondary data is systematically collected from various authentic literature to reconstruct past events. The analysis is conducted using a historical sociology approach to explore the causal relationship among modernization, religion, and social change. The results of the study show that the Iranian Revolution was triggered by the White Revolution policy, which tended to be top-down and westernization, thus creating economic disparities and socio-religious tensions. Intellectually, the integration of the concept of Wilayat al-Faqih by Ayatollah Khomeini and the thoughts of Ali Shari'ati succeeded in transforming the Shia tradition into an effective political ideology in mobilizing the masses. Post-revolution, Iran underwent a complete restructuring, encompassing an Islamic-based education system, a strengthening of theocratic-democratic identity, and the implementation of a strategy of economic resistance in the face of international sanctions. Despite successfully achieving national independence, the current regime faces challenges of dual identity among the younger generation and complex macroeconomic pressures. Keywords: Intellectual Genealogy, Iranian Revolution 1979, Wilayat al-Faqih